Doramectin efficacy against Psoroptes ovis in sheep: Evaluation of pharmacological strategies - Larroza, Marcela Patricia; Soler, Paula; Robles, Carlos Alejandro; Cabrera, Francisco Raúl; Ballent, Mariana; Lanusse, Carlos; Lifschitz, Adrian Luis (Elsevier, 2020)
The aims of this study were to evaluate the efficacy of two injectable formulations of doramectin (DRM) against Psoroptes ovis in sheep infested under controlled experimental conditions and to characterize the DRM plasma disposition kinetics in the infested animals. To this end, sheep were experimentally infested with a P. ovis strain from a farm with a history of treatment failure, and then treated either with DRM 1% (traditional preparation) on days 0 and 7 or with DRM 3.15% (long-acting formulation) on day 0. The efficacy of each treatment was calculated by counting live mites in skin scrapings. Plasma samples were obtained from each animal and DRM concentrations were measured by HPLC. After the two doses of DRM 1%, the maximum efficacy (98.8%) was reached on day 28, whereas after the single dose of DRM 3.15%, the maximum efficacy (100%) was reached on day 35 and ratified on day 42. The longacting formulation allowed obtaining higher exposure and more sustained concentrations of DRM than the traditional preparation. Although both DRM formulations studied were effective according to international protocols, they did not reach 100% effectiveness in the time required for approved pharmaceutical products against sheep scab, according to Argentine regulations.